2018
DOI: 10.1007/s11104-018-3568-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar on carbon and nitrogen fluxes in boreal forest soil

Abstract: Background and aims The addition of biochar to soil may offer a chance to mitigate climate change by increasing soil carbon stocks, improving soil fertility and enhancing plant growth. The impacts of biochar in cold environments with limited microbial activity are still poorly known. Methods In order to understand to what extent different types and application rates of biochar affect carbon (C) and nitrogen (N) fluxes in boreal forests, we conducted a field experiment where two different spruce biochars (pyrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 79 publications
7
41
0
1
Order By: Relevance
“…During the initial stage of biochar incubation, microbial assimilation of the labile C associated with biochar could have led to an increased immobilization of N into microbial biomass. Past studies have shown higher microbial biomass growth with biochar addition [74][75][76]. Nevertheless, the recycling speed of organic matter seems to be similar among soils with and without biochar after 3 months of incubation, with the turnover of small organic N not affect by biochar.…”
Section: Discussionmentioning
confidence: 93%
“…During the initial stage of biochar incubation, microbial assimilation of the labile C associated with biochar could have led to an increased immobilization of N into microbial biomass. Past studies have shown higher microbial biomass growth with biochar addition [74][75][76]. Nevertheless, the recycling speed of organic matter seems to be similar among soils with and without biochar after 3 months of incubation, with the turnover of small organic N not affect by biochar.…”
Section: Discussionmentioning
confidence: 93%
“…As a regenerable adsorbent, biochar could be used as a soil amendment following the adsorption-based water purification. Biochar addition has been found to improve soil properties and the growth of crops and trees (Biederman and Harpole 2013;Lehmann and Joseph 2015;Palviainen et al 2018), and nutrients adsorbed onto biochar are easily available for plants when placed in the soil (Taghizadeh-Toosi et al 2012). Therefore, the utilization of biochar as an adsorbent can further improve its potential as a soil amendment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous laboratory experiments indicate that biochar can adsorb compounds from water; however, these experiments have typically been done for single compounds, whereas simultaneous adsorption of several compounds from natural waters has not been studied before. As multiple compounds compete simultaneously for the adsorption places in the adsorption process (Palviainen et al 2018), all dissolved compounds in the water can affect the performance of biochar in nutrient reclamation. The chemical composition and nutrient concentrations of peatland forest runoff water differ significantly from agricultural or urban runoff waters (Oliveira et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…After biochar is saturated with nutrients, it can be used for soil amendment. Biochar addition improves soil properties, increases carbon sequestration, reduces the need for fertilizers and improves the growth of trees [45,[86][87][88]. Thus, biochar could offer an innovative, inexpensive, renewable and 100% recyclable material for water purification and nutrient recycling, thereby allowing the responsible utilization of natural resources.…”
Section: Biochar As a Water Protection Toolmentioning
confidence: 99%
“…Consequently, biochar can provide a lower cost alternative to activated carbon [41,42]. Biochar has many applications in environmental management and has been used in soil conditioning, soil remediation and carbon sequestration [43][44][45]. In recent years, there has been increasing interest in using biochar in contaminant removal from agriculture and urban runoff water [46].…”
Section: Introductionmentioning
confidence: 99%